The Scaling Mindset – Shifting from Problems to Solutions. Insights from the Review of CCAFS Scaling Activities, 2019 - Koerner, Jana; Theissen, Arne H.; Loboguerrero Rodriguez, Ana María; Campbell, Bruce M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
In the frame of the review of CCAFS scaling activities in 2019, 21 project leaders and –implementers were interviewed about their scaling processes, touching a series of aspects that had been identified as crucial and/or critical by earlier research. Results were analysed with a systemic approach, to draw organisational learnings. The findings were validated with CCAFS core team during their Scaling Workshop in Madrid, May 2019, in which the Core Team also prioritized its programmatic areas of response. This working paper captures the main insights and learnings from both the interviews on project level, followed by the results’ analysis. It then summarized the Core Team workshop’s main discussion points and shortly outlines the programmatic areas of response that CCAFS identified. The learnings and insights on the realities of scaling agricultural innovations presented in this working paper can provide a rich basis for further synthesis and/or deeper research on the different aspects of innovation development and scaling.